Establishment of Dissolution Kinetics and Mechanism of Direct Leaching of Gagi Phosphate Rock in Hydrochloric Acid Solution - Ayinla, K.I.; Baba, A.A.; Oyinloye, J.S.; Olaoluwa, D.T.; Ibrahim, A.S.; Raji, M.A.; Abdulrahman, A.; Ajetomobi, O.O. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2018)
Hydrochloric acid leaching kinetics of Gagi phosphate rock assaying 36.1% P2O5, 4.3% Al2O5, and 3.9% SiO2 wasexamined. The phosphate rock mineralogical characterization indicated that the major phase of the rock was Quartz (SiO2)with calcium aluminum phosphate as the major phosphate ore. The effect of different optimization parameters such aslixiviant concentration, system temperature, ore particle size and stirring speed were investigated. At selective extractedduration of 2 h with standard leaching condition of -70 + 63µm, 80°C, 0.20 M HCl and 300 rpm stirring speed, more than84% P2O5 could be achieved. The leaching process kinetic mechanism was found to be surface diffusion controllingmechanism. The calculated reaction order and activation energy was 0.789 and 42.31 kJ/mol respectively. In addition, amathematical expression including the experimental parameter to represent the kinetic of this leaching process wasproposed in the study.